2008
DOI: 10.1177/1753193407087862
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Elbow Position on the Range of Supination and Pronation of the Forearm

Abstract: A kinematic study was performed to examine the influence of elbow position on the range of supination and pronation of the forearm. The ranges of supination and pronation were measured in 50 volunteers (25 men and 25 women) using a custom-designed jig which constrained unwanted and confounding movements of the limb. Measurements were taken with the elbow in full extension, 45 degrees flexion, 90 degrees flexion and full flexion. The data showed a reciprocal relationship between the range of supination and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
(6 reference statements)
5
24
0
Order By: Relevance
“…Some studies have poor methodologic quality [33]. In others the experimental protocol does not reflect day-to-day use of the UG [7,11,28]. Some authors also omit detailing the population, instruments, measurement methods, or protocol when reporting UG use, making it harder to assess reliability of the UG [1,12].…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have poor methodologic quality [33]. In others the experimental protocol does not reflect day-to-day use of the UG [7,11,28]. Some authors also omit detailing the population, instruments, measurement methods, or protocol when reporting UG use, making it harder to assess reliability of the UG [1,12].…”
Section: Introductionmentioning
confidence: 98%
“…This finding is consistent with Shaaban. 11 As for velocity, subjects recorded higher velocity during pronation at 180 EE and higher velocity during supination at 90 EE although the ROM during 90 EE is bigger than 180 EE. The ROM of both pronation and supination of female were higher than male.…”
Section: Discussionmentioning
confidence: 91%
“…11 Shaaban reported that ROM of supination in the non-dominant hand was higher than dominant hand when the elbow was extended and the shoulder fixed to 90 flexion. Baseball and tennis players showed increased shoulder lateral rotation in dominant arm but reduced medial rotation.…”
Section: Discussionmentioning
confidence: 98%
“…The changes would have contributed to error in the extracted orientation angle and were probably a source of some of the noise in Fig.6b (rotated signal). The flex-extend process could also explain the limited range of measured roll at the wrist (Tables 2&4) as a fully flexed elbow limits forearm pronation and a fully extended elbow limits forearm supination [6]. The flex-extend exercise would result in these limits applying concurrently.…”
Section: Discussionmentioning
confidence: 97%